(3GdJbGSje hGdCfhGY aj GdMOjKs - (3CHh MGJe eMeO Hf MHGf GdJejej GdHSJjs
(3ChdgG (B:s
(3jHOC HGdfhY GdJGSY Yf GNHGQg Udi Gddg Ydjg hSde s
(3BNQgG (B:s
(3Yf GHf YeQ Gf GdYHGS Hf YHO GdeWdH GSJCPf GdfHi Udi Gddg Ydjg hSde Gf jHjJ Hecg djGdi efi ef GLd GdSbGjI aGPf dg ef GLd GdSbGjg BNQ GdeLdO GdKGdK ef GdJbGSje hGdGfhGY dCHi MGJe Hf MHGf s
(3GdfSNI HgG MhGTs
(3YdjgG SeGYGJs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B463s
Keywords: (3GdMOjK h GdeUWdMs